2012
DOI: 10.2754/avb201281020163
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of melamine and cyanuric acid residues in eggs from laying hens exposed to contaminated feed

Abstract: The aim of this study was to monitor the carry-over of melamine and its metabolite cyanuric acid from melamine-contaminated feed administered to layers into eggs. Ten experimental Isa Brown layers (36 week of age) were fed melamine-contaminated feed containing 100 mg of melamine per kg of feed. The duration of the experiment was 6 weeks. Eggs were collected during whole experiment. Analysis of eggs was done by a simple extraction of melamine and cyanuric acid residues, using a water-acetonitrile mixture and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Suchy et al (2014) reported that in laying hens not only melamine was stored in their tissues, but it was also biotransformed into cyanuric acid which had not been confirmed in poultry before. The experimental administration of melamine contaminated diets to laying hens also resulted in the excretion of some part of melamine into eggs (Bai et al 2010;Novak et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Suchy et al (2014) reported that in laying hens not only melamine was stored in their tissues, but it was also biotransformed into cyanuric acid which had not been confirmed in poultry before. The experimental administration of melamine contaminated diets to laying hens also resulted in the excretion of some part of melamine into eggs (Bai et al 2010;Novak et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The degradation of amoxicillin and tetracycline was reported by this technique (Novak et al 2012;Safari et al 2015;Wang and Jian 2015). In the case of amoxicillin, the sulfate radicals are produced using ultrasound-activated oxone in the presence of cobalt ion.…”
Section: Addition Of Radical Promotermentioning
confidence: 98%
“…The COD removal enhanced with the addition of oxone and Co 2? and also with the applied power of ultrasound to an optimum power of 300 W. The removal of this kind of pollutants using sulfate radical anion in the presence of ultrasound is thus encouraging (Novak et al 2012).…”
Section: Addition Of Radical Promotermentioning
confidence: 98%
“…When melamine is present in feed, it can be transferred into eggs, at a carry-over rate of approx. 0.5-1.5% (Gallo, Bertuzzi et al 2012, Novak, Suchy et al 2012, Lorenz, Fry et al 2014. Melamine might also enter the egg production chain at the egg processing stage as a result of its illegal addition to food products in order to boost their protein content or as a contact material.…”
Section: Melamine Received Considerable Public Attention After the Pementioning
confidence: 99%
“…Melamine might also enter the egg production chain at the egg processing stage as a result of its illegal addition to food products in order to boost their protein content or as a contact material. Melamine is converted to cyanuric acid, which is deposited in eggs at a similar concentration as melamine (Novak, Suchy et al 2012).…”
Section: Melamine Received Considerable Public Attention After the Pementioning
confidence: 99%